Total arsenic analysis in Californian wines with hydride generation – microwave plasma – atomic emission spectroscopy (HG-MP-AES). Issue 6 (27th April 2016) - Tanabe, C. K.; Hopfer, H.; Gilleland, G.; Liba, A.; Ebeler, S. E.; Nelson, J.
Abstract : A new method was developed to determine total As in wine with HG-MP-AES with detection limits of 0.38 μg L −1 . Abstract : The total arsenic concentrations of forty Californian wine samples were analyzed using a novel hydride generation-microwave plasma atomic emission spectroscopy (HG-MP-AES). Prior to analysis, various arsenic species were reduced with potassium iodide, and detected as gaseous arsenic trihydride. The method detection limit was determined to be 0.38 μg L −1 . Total arsenic levels of the different tested wine styles (white, rose, red, Port, sparkling) ranged from below the detection limit to 43.8 μg L −1 . The developed method provides quick and reliable quantitation of total arsenic content for a variety of wine styles down to levels below the EPA drinking water limit (10 μg L −1 ). This is the first report of HG-MP-AES, utilizing the Multimode Sample Introduction System (MSIS), for the determination of total arsenic.